2008
DOI: 10.1093/jpe/rtn009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial isolation and genetic differentiation in naturally fragmented plant populations of the Swiss Alps

Abstract: Aims The effect of anthropogenic landscape fragmentation on the genetic diversity and adaptive potential of plant populations is a major issue in conservation biology. However, little is known about the partitioning of genetic diversity in alpine species, which occur in naturally fragmented habitats. Here, we investigate molecular patterns of three alpine plants (Epilobium fleischeri, Geum reptans and Campanula thyrsoides) across Switzerland and ask whether spatial isolation has led to high levels of populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
5
30
3
Order By: Relevance
“…Leptogalium confirmed the current taxonomic division proposed by Ehrendorfer (1960) on the basis of their morphological characters. The studied species have similar values of mean genetic diversity (FST) which is in concordance with these of other species characterized by narrow geographical range, a relatively narrow ecological scale and a natural fragmentation of population, as Campanula thyrsoides and Epilobium fleischeri (Kuss et al 2008), Eryngium alpinum (Gaudeul et al 2000). These values correspond also with these of species included in literature into the group of "long-lived perennials" (Nybom 2004), the group to which the studied Galium species undoubtedly belong.…”
Section: Discussionsupporting
confidence: 84%
“…Leptogalium confirmed the current taxonomic division proposed by Ehrendorfer (1960) on the basis of their morphological characters. The studied species have similar values of mean genetic diversity (FST) which is in concordance with these of other species characterized by narrow geographical range, a relatively narrow ecological scale and a natural fragmentation of population, as Campanula thyrsoides and Epilobium fleischeri (Kuss et al 2008), Eryngium alpinum (Gaudeul et al 2000). These values correspond also with these of species included in literature into the group of "long-lived perennials" (Nybom 2004), the group to which the studied Galium species undoubtedly belong.…”
Section: Discussionsupporting
confidence: 84%
“…In all two species, we found that genetic connectivity among populations decreases with increasing spatial distance: a result of natural fragmentation. Indeed, as revealed in Campanula thyrsoides L., Epilobium fleischeri Hochst., and Geum reptans L. by Kuss et al, 50 the plots showed that populations grouped without overlap agreed with their geographical location as supported by AMOVA. The PCoA plot of C. rapunculoides genotypes clearly demarcated the differences between the four populations.…”
Section: Discussionmentioning
confidence: 67%
“…Many studies have shown that spatial isolation and small population size may negatively affect many rare plant species, limiting genetic exchanges between populations, reducing plant fitness and viability, and increasing the risk of extinction (Young, Boyle and Brown 1996;Frankham and Ralls 1998;Lu, Waller and David 2005;Leimu et al 2006;Aguilar et al 2008;Kuss et al 2008). Nonetheless, natural fragmentation is a frequent feature in alpine species, due to the effects of Quaternary history, pronounced mountainous topography and related abiotic heterogeneity (Kuss et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, natural fragmentation is a frequent feature in alpine species, due to the effects of Quaternary history, pronounced mountainous topography and related abiotic heterogeneity (Kuss et al 2008). Diverse life history traits of different plants may make them more or less vulnerable to fragmentation effects, i.e.…”
Section: Introductionmentioning
confidence: 99%